(untitled) (KULT_online, 2011)
Peter Thomas’s The Gramscian Moment provides a definitive rebuttal of Perry Anderson’s and Louis Althusser’s influential critiques of the work of Antonio Gramsci. Throughout the course of the book, which ranges from discussions of the literary form of the Prison Notebooks to explications of the concepts of ’passive revolution’ and the ’integral state’ he demonstrates that Gramsci’s work is characterized by ’absolute historicism’, ’absolute immanence’ and ’absolute humanism’. Hegemony, that is, constitutes a ’metaphysical event’ or a ’philosophical fact’: the passage between these last two conceptions delineates the ’Gramscian moment’ of 1931-1932.